2017
DOI: 10.1136/heartjnl-2017-311738
|View full text |Cite
|
Sign up to set email alerts
|

Renin–angiotensin system blockade therapy after transcatheter aortic valve implantation

Abstract: Postoperative RAS blockade therapy is associated with greater LV mass index regression and reduced all-cause mortality. These data need to be confirmed by a prospective randomised controlled outcome trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 30 publications
1
39
0
Order By: Relevance
“… 58 The Optimised CathEter vAlvular iNtervention-transcatheter aortic valve implantation (TAVI) registry also showed that using propensity score-matched cohort analysis, patients with RAASi postoperatively had greater LVH regression than without (mean change in LV mass index of −9 vs −2 g/m 2 , p=0.024) in 6 months post-AVR. 47 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 58 The Optimised CathEter vAlvular iNtervention-transcatheter aortic valve implantation (TAVI) registry also showed that using propensity score-matched cohort analysis, patients with RAASi postoperatively had greater LVH regression than without (mean change in LV mass index of −9 vs −2 g/m 2 , p=0.024) in 6 months post-AVR. 47 …”
Section: Resultsmentioning
confidence: 99%
“…58 The Optimised CathEter vAlvular iNtervention-transcatheter aortic valve implantation (TAVI) registry also showed that using propensity score-matched cohort analysis, patients with RAASi postoperatively had greater LVH regression than without (mean change in LV mass index of −9 vs −2 g/m 2 , p=0.024) in 6 months post-AVR. 47 Safety outcomes post-AVR Overall, post-TAVI, the risk of acute kidney injury was not significantly lower in patients on AHT compared with controls (RR 0.80, 95% CI 0.35 to 1.84, p=0.47), but substantial heterogeneity was demonstrated (I 2 =53%). An RCT called the PROphylactic effect of frusemide-induCed diuresis with matched isotonic intravenous hydraTion in TAVI showed that frusemide-induced diuresis reduced incidence of acute kidney injury post-TAVI, but the duration of follow-up was only 30 days.…”
Section: Overall Random Effectmentioning
confidence: 95%
“…Also, one single study has analysed retrospectively the effects of RAS blockade in patients harbouring a TAVI device suggesting that this therapy could be associated with greater left ventricular mass index regression and reduced all-cause mortality. 32 However, any randomised trial has confirmed this hypothesis. The RASTAVI Study is the first formal attempt to clarify the role of RAS inhibitors in the prognosis of these patients.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Furthermore, the capability of ACEI/ARB to attenuate also myocardial fibrosis [56], presumably less responsive to post-procedural afterload reduction than myofibrillar hypertrophy, is especially promising in post-TAVI patients, because the extent of preoperative-myocardial fibrosis predisposed to the post-operative persistence of residual LVH [38]. In a registry of 1,215 patients undergoing TAVI, Ochiai et al [63] recently demonstrated 4-fold higher 6-month regression of LV mass (9% vs. 2%) and over 2-fold lower all-cause 2-year mortality in patients treated with ACEI or ARB after the procedure.…”
Section: Renin-angiotensin System Blockade In As – a Tool To Inhibit mentioning
confidence: 99%